Precision of 3D MSCT Scan Diagnostcs on Maxillofacial Trauma Compared to Stabilization and Instrumentation Operation Results - Meitty Christina Hidayati (Institute of Medico-Legal Publishers, 2020)
Handling standardized radiological readings of patients with maxillofacial trauma, particularly in radiology are currently absent. Appropriate and accurate of radiological reading results could be as the guideline for surgeons in determining surgical procedures. This study aimed to evaluate the diagnostic accuracy of maxillofacial fracture patients with head 3D CT scan compared to stabilization and instrumentation results as gold standard. Secondary data that derived from medical records were used as 29 patients with clinical maxillofacial trauma enrolled in this study at Radiology Section of Dr.Soetomo General Hospital from November 2012 to March 2013. The Mc Nemar test showed that there was no significant difference between the 3D CT scan results and the stabilization also instrumentation results with p = 1.000 (p> 0.05). While, the result was by calculating Kappa coefficient that a high suitability between head 3D CT scans and stabilization also instrumentation result with κ = 1.000, p = 0.000 (p <0.05).There were several complications in the form of Cranii Bone Fraktur (25%), intracranial complication (15.24%), Haematosinus (52.38%) and Soft tissue haematoma (32.38%) with most intracranial complications ICH (31.25%), then, most soft tissue complications were in the Orbita region (26.47%) and the most common Haematosinus complications regarding Sinus Ethmoid and Maksilaris (29.09%). It concluded that the 3D CT scan results were in accordance with the results of stabilization and instrumentation operations.